Importance of allochthonous matter for profundal macrozoobenthic communities in a deep oligotrophic lake1. Issue 1 (19th February 2013) - Fuentes, Norka; Güde, Hans; Straile, Dietmar
Abstract This study evaluates the nutritional importance of allochthonous matter supply for profundal macrozoobenthic communities and determines abundances and carbon sources used by chironomids and oligochaetes at two sampling sites with different allochthonous contributions, in the deep oligotrophic waters of Lake Constance. Site AL, characterized by sedimenting organic matter (POMsed) with a more allochthonous origin was dominated by oligochaetes, whereas site AU characterized by POMsed of predominantly autochthonous origin, was dominated by chironomids. Total macroinvertebrate abundances were 10–20 times higher at site AL compared to site AU. At site AL microbial biomass per gram dry sediment (indicated by ATP content and bacterial abundances) was lower, whereas microbial activity (incorporation of leucine, respiration of glucose) was higher than at site AU. A higher metabolic activity at site AL was also indicated by steeper oxygen gradients in sediment microprofiles. Mean δ13C stable isotope signatures of oligochaetes (δ13C = −33.24 ± 1.27‰) and, to an even greater extent, of the dominant chironomid Micropsectra sp. (δ13C = −40.08 ± 1.65) at site AL were depleted compared to site AU for oligochaetes (δ13C = −30.19 ± 0.60‰) and chironomids (δ13C = −30.40 ± 0.75‰). At site AL, mean δ13C values of chironomids and oligochaetes were 11‰ and 4‰ lower, respectively, than mean POMsedδ13C. At site AU, benthic macroinvertebrates and POMsed were of comparable magnitude. The lower invertebrate δ13C values at site AL suggest an increased contribution of methane oxidizing bacteria (MOB) to the diet of the benthic organisms. A mixing model based on stable carbon isotopes suggests that at site AL 21 to 44% of chironomid diet and 9 to 19% of oligochaete diet stems from MOB consumption, whereas calculated MOB consumption was zero at site AU. Mean δ15N values of chironomids and oligochaetes were higher at both sites compared to POMsed, but at site AL (oligochaetes = 7.07 ± 0.61‰, "Micropsectra sp." = 8.62 ± 0.30‰) the difference was less pronounced than at site AU (oligochaetes = 13.71 ± 0.30‰, "Micropsectra sp." = 14.00 ± 0.95‰). These differences are considered to reflect mainly the degree of biotic processing of POMsed before consumption by invertebrates. Given that autochthonous POMsed, i.e. chlorophyll sedimentation, was comparable at both sites, but differences were observed with respect to total POMsed sedimentation rates, δ13C and δ15N isotope signatures of POMsed, and microbial activities in the sediments, we suggest that there is a strong contribution of allochthonous POMsed supply to the nutrition of macrobenthic communities at site AL. This suggests that allochthonous carbon supply is at least partly bioavailable and stimulates microbial growth and metabolic activities in lake sediments, which in turn provides additional nutritional sources for benthic organisms. Furthermore, the example of Lake Constance shows that, even in a well‐oxygenated oligotrophic lake, at least part of the allochthonous POMsed is made available to higher trophic levels via methane production and MOB biomass.